ChemInform Abstract: A Novel Tunnel Na0.61Ti0.48Mn0.52O2 Cathode Material for Sodium‐Ion Batteries. Issue 35 (2nd September 2014) - Guo, Shaohua; Yu, Haijun; Liu, Dequan; Tian, Wei; Liu, Xizheng; Hanada, Nobuko; Ishida, Masayoshi; Zhou, Haoshen
Abstract The title material is synthesized by solid state reaction of Na2CO3, Mn2O5, and TiO2 (Ar, 900 °C, 20 h).